Busulfan, melphalan, and bortezomib compared to melphalan as a high dose regimen for autologous hematopoietic stem cell transplantation in multiple myeloma: long term follow up of a novel high dose regimen. Issue 14 (5th December 2020) - Hagen, Patrick; D'Souza, Anita; Hari, Parameswaran; Davila, Omar; Zhang, Mei-Jie; Vesole, David H.; Smith, Scott E.; Rodriguez, Tulio E.; Stiff, Patrick J.
Abstract: Melphalan at a dose of 200 mg/m 2 (MEL200) remains the standard high dose therapy before autologous stem cell transplantation (ASCT) for multiple myeloma (MM). Intensifying the high dose regimen has shown promising results. We report here 7-year follow up of our novel high dose regimen of busulfan and melphalan followed by bortezomib (BuMelVel). Forty-three MM patients received BuMelVel high dose therapy with pharmacokinetic adjusted busulfan. Outcomes were compared to a matched control cohort from the CIBMTR database ( n  = 162) receiving MEL200. The primary endpoint was progression free survival. Five year PFS was 47% v 30% (95% CI; 32–62) in favor or the BuMelVel group (95% CI; 23–37) ( p  = 0.05). In multivariate analysis for PFS, BuMelVel (HR 0.65; 95% CI 0.44–0.97)( p  = 0.036) was predictive. Similar to recent reports of double alkylator therapy, although depth of response was similar between the BuMelVel group and MEL200, the BUMELVEL group experienced an improved PFS.